CREATE AND EVALUATE A TEMPERATURE MONITORING SYSTEM IN THE CONDITIONER IN PELLETED FEED - AL-Chalabi, Dhia Ahmed (Diyala Agricultural Sciences Journal, 2016)
This project has been conducted in New Zealand in 1999, as a requirement for feed production companies to control salmonella in feed by Ministry of Agriculture and Fisheries (MAF). Feed is the most important factor in poultry production enterprises because of its impact on cost and health. It takes the feed about two minutes to reach the 80 ºC. The feed could be recycled if didn’t reach the 82-83 ºC planned. Steam temperature was stable and around 130 ºC. This temperature could be optimized to reduce energy cost without affecting the pelleting process through tracing the feed in temperature (ingredients) one can say, that some of the steam is entering to the feed-in tube and raising the feed-in temperature to 46-50 ºC. The regular incoming feed temperature was between 20-25 ºC. The die temperature was 92 ºC, and cooler temperature for the feed out was 20 ºC.